"Write a Word, Get a Third": Managing Conflict and Rewards in Professional Songwriting Teams. (May 2015) - de Laat, Kim
This article examines the doubly uncertain work environment of professional songwriters: They are affected by wider events in the music industry, and their immediate work context is a team setting where the distribution of tasks varies from one project to the next. Interviews reveal that songwriters pursue professional interests by enhancing cooperation, rather than engaging in defensive tactics. The author identifies two conventions: equal authorship and professional conciliation. Such conventions elucidate how rewards are managed in a team context of task variation and underscore the mutually constitutive relationship between conflict and cooperation within postbureaucratic forms of organizing.